Laboratory Evaluation of Pseudomonas Aeruginosa Distribution and Diagnosis in Clinical Samples - Maesm Ahmed Mohamed Ben Hsin; Nagla T. T. Arab; Hamza Ahmed Mohammad Emsaed; Ahmed Ramadan Abujarida (Journal of Scientific and Human Dimensions, 2025)
This study analyzed the prevalence and characteristics of bacterial infections, focusing on Pseudomonas aeruginosa, using 58 clinical samples from Al-Jalaa Hospital and Al-Sharq Laboratory. The results revealed a clear dominance of Pseudomonas bacteria, which were isolated from 50 of the 58 total samples, accounting for 86.21% of the cases. Younger age groups were the most affected, with children aged 6-10 years showing the highest proportion of cases (24.0%). A higher prevalence was also observed among females, who accounted for 44 of the 50 positive cases (88.0%). Additionally, urine samples were the most frequently collected specimen type, making up 37.9% of the total samples. Antimicrobial susceptibility testing was performed on 50 clinical isolates of Pseudomonas. The results showed that Colistin was the most effective antibiotic with 96% susceptibility, followed by Amikacin (80%) and Imipenem (60%). In contrast, high resistance rates were observed against Ceftazidime (52%), Ciprofloxacin (50%), and particularly Piperacillin (86%), highlighting the limited effectiveness of these agents for empirical therapy
Keywords: Bacterial infections; Clear dominance; Children; urine samples; Antimicrobial susceptibility testing